UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING PADA MATERI INDONESIA KAYA BUDAYA DI KELAS IV SDN TANAH TINGGI 09 JAKARTA PUSAT - Dinda Ajeng Ayu Lestari; Julius Sagita; Indah Trismawanti (STKIP Subang, 2023)
This study aims to increase the learning activity of fourth grade students at SDN Tanah Tinggi 09 Jakarta with a total of 24 children consisting of 8 male students and 16 female students through the Problem Based Learning model in the Natural Sciences subject on Indonesia Rich Culture by describing activities learning carried out by students and teachers. The research method used is Classroom Action Research (CAR) or Classroom Action Research. The achievement of this research was obtained from the results of observations using research instruments in the form of observation sheets of students' and teachers' activities. Based on the results of observations by doing it for 2 cycles, the research shows that the learning activity of students has increased after learning using the Problem Based Learning model in science learning. The increase can be seen from the completeness of the activities of students and teachers, where teacher activity in cycle I was 76.5%, then in cycle II it increased to 84%. Student activity in cycle I was 72%, then increased in cycle II by 83%. From the observational data obtained where in the learning process activities focus more on the teacher. After the improvement, students look very active during the learning process.